PARADOXES OF PERSONALITY IN THE PAGES OF GEORGII EFRON’S DIARY - Steven, Gabriel; Krylov , Viacheslav; Mikhailova, Maria (Revista Inclusiones, 2019)
As a genre, the diary provides rich material for analyzing the contradictions of a personality. In accord with other researchers of the genre, the diary’s most important function (especially those kept between the ages of 14 and 25) is psychological: it substitutes or compensates for parts of the author’s psyche that do not find release in other forms; it allows the writer to voice hidden spiritual needs. The diary provides a unique chance to express the zigzagging thoughts of a person at a given moment, and to understand the hidden essence of a person. It is no accident that Kafka willed that under no condition should his diaries ever be published.